2018
DOI: 10.1371/journal.pone.0199979
|View full text |Cite
|
Sign up to set email alerts
|

Bank1 and NF-kappaB as key regulators in anti-nucleolar antibody development

Abstract: Systemic autoimmune rheumatic disorders (SARD) represent important causes of morbidity and mortality in humans. The mechanisms triggering autoimmune responses are complex and involve a network of genetic factors. Mercury-induced autoimmunity (HgIA) in mice is an established model to study the mechanisms of the development of antinuclear antibodies (ANA), which is a hallmark in the diagnosis of SARD. A.SW mice with HgIA show a significantly higher titer of antinucleolar antibodies (ANoA) than the B10.S mice, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…In human T cells, both methyl mercuric chloride and inorganic Hg induce mitochondrial dysfunction and glutathione depletion (17), leading to generation of reactive oxygen species (ROS) and apoptotic caspases (18). Another study using A.SW mice showed significantly lower Bank 1 (B-cell scaffold protein with ankyrin repeats 1) gene expression and higher NF-kB, TLR-9, IL-6, and TNF-α after Hg exposure, supporting the roles of Bank1 (produced mainly in B cells) and NF-kB as the key regulators of antinucleolar antibodies in HgIA (19).…”
Section: Mercurymentioning
confidence: 92%
“…In human T cells, both methyl mercuric chloride and inorganic Hg induce mitochondrial dysfunction and glutathione depletion (17), leading to generation of reactive oxygen species (ROS) and apoptotic caspases (18). Another study using A.SW mice showed significantly lower Bank 1 (B-cell scaffold protein with ankyrin repeats 1) gene expression and higher NF-kB, TLR-9, IL-6, and TNF-α after Hg exposure, supporting the roles of Bank1 (produced mainly in B cells) and NF-kB as the key regulators of antinucleolar antibodies in HgIA (19).…”
Section: Mercurymentioning
confidence: 92%
“…[14] Recent studies have shown that Bank1 and NF-κB subunit 1 played critical regulatory role in antinucleolar antibodies in mercuryinduced autoimmunity in mice. [15] However, the association of IKBKE and BANK1 gene polymorphisms of SLE in the Han population of southwest China remained unclear. Based on this background, this study investigated the association of IKBKE rs15672 and BANK1 rs12640056 gene polymorphisms and susceptibilities of SLE in Han population of southwest China.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, researchers published various results that did not always correlate between papers [153]. This is because Hg triggers an autoimmune manifestation that is dose, time, gender and strain dependent [41,154]. This can be solved by calculating the internal Hg dose in mice, but the internal dose differs most of the time between studies.…”
Section: Discussionmentioning
confidence: 99%
“…These tandem repeats are found throughout the genome composed of di-, tri-, tetra-or bigger repeats (Fig 2). Genes are co-segregated with the highly polymorphic microsatellites, which make them useful markers for mapping studies [38][39][40][41]. SNPs occur naturally in the human population and is a variation of a single nucleotide replaced with different nucleotide.…”
Section: Genome Wide Association Studymentioning
confidence: 99%
See 1 more Smart Citation